Women’s role in leading organizations - Alecxandrina DEACONU; Lavinia RAŞCĂ (Revista de Management Comparat International)
Good leadership became very important for employees’ engagement and productivity, while companies where women are promoted in leadership positions enjoy very good economic results. Starting from these facts, the authors focused their research on studying a triangle of concepts: leadership, gender, generation, aiming to understand which the characteristics of women leaders are, how they are different from those of men leaders, and how the role and importance of women leaders are perceived by different generations of employees. The authors, aiming to check the hypothesis that female leadership is valuable in modern organizations, reviewed the literature, were inspired by the ten descriptors presented by Kouzes and Posner (Checklist of Admired Leaders, 2002) as being the characteristics of successful leaders, and conducted a quantitative research. They developed a questionnaire and sent it out to employees of large companies in Romania. The data were processed with the SPSS program (Statistical Package for the Social Sciences). The research results show differences in perceptions related to this topic between male and female respondents, between those holding different positions in the organizations, and between generations. Similarities and differences between women and men as leaders were also revealed. Starting from the findings of the research, the authors made some recommendation for improving leadership within organizations, pointing out the need of a balance between men and women at the top.